Mechanisms of deposit formation in injection moulding cavities and the role of tool coatings and internal release agents - Lingnau, Kai; Theile-Rasche, Chantal; Vissing, Klaus; Moritzer, Elmar; Grundmeier, Guido; Wiesing, Martin (Surface and Coatings Technology)
Keywords: Plasmabeschichtung; Spritzgießen; Spritzgießwerkzeug; Trennschicht; ultraTrenn; Werkzeugbeschichtung

Fiber-matrix adhesion in glass fiber reinforced thermoplastic composite laminates and its effect on mechanical properties - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Claes, Leander; Wippermann, Mareen; Haag, Markus; Gries, Thomas; Henning, Bernd (International Polymer Processing)
With the growing demand for lightweight solutions to reduce emissions, especially in the transportation, automotive and aerospace sectors, recyclable, continuous fiber-reinforced plastic composite laminates with a thermoplastic matrix are of rising interest. To achieve their maximum mechanical properties, the fiber-matrix adhesion (FMA) is critical. In this work, continuous fiber-reinforced thermoplastic laminates (CFRTPL) with a polypropylene (PP) matrix and twill woven glass fiber fabrics are produced by film stacking. The films used contain different amounts of maleic-anhydride-grafted PP (MA-g-PP) as a coupling agent to produce CFRTPL of different mechanical strengths. To analyze the FMA, the CFRTPL are subjected to Charpy-impact and tensile tests. Additionally, single fiber pull-out tests (SFPT) are conducted to further investigate the effect of MA-g-PP on the FMA. The results of the SFPT show an improvement in apparent interfacial shear strength (AIFSS) when the MA-g-PP content is increased, which can be attributed to an increase in FMA. However, the research shows that MA-g-PP has a low impact on the mechanical properties if the force is applied parallel to the warp and weft threads during tensile testing and the results of the Charpy-impact testing suffer from embrittlement of the matrix material. Subsequently, the results of this study are compared to three-point flexural tests conducted in a previous study. It can be concluded that tensile and impact tests are not suited to investigate FMA on a macroscopic scale, while SFPT and flexural tests provide a better alternative.

Determination of the unit cell geometry in fibre-reinforced polymer sheets using guided acoustic waves - Wippermann, Mareen; Claes, Leander; Brandes, Philipp; Moritzer, Elmar; Henning, Bernd
Woven fibre-reinforced polymers are used in a variety of application, especially where a low mass to stiffness ratio is required. Of paramount importance for the tailored mechanical properties these composite materials exhibit is the type and geometry of the fibre weave. Especially continuous fibre-reinforced thermoplastic composites are fabricated as laminates and subsequently exposed to forming processes which alter the geometry of the fibres unit cell and thus the local mechanical properties of the material. An approach utilising broadband ultrasonic waves is proposed to non-destructively determine the geometry of the unit cell of the weave. The dispersive behaviour of woven fibre-reinforced sheets is described in accordance with the Flouquet-Bloch theorem as a phononic crystal. In order to develop a model for a description of these periodically structured waveguides, the smallest repeating unit of the wave is modelled with periodic boundary conditions. The resulting dispersion diagram exhibits similarities to that of a homogeneous plate, but additionally displays a periodicity in the wavenumber regime, which correspond with the size of the unit cell. Experimental studies of the dispersive behaviour of acoustic waves in woven fibre-reinforced samples also show a periodicity in the wavenumber regime, enabling a measurement procedure of the unit cell geometry.

Assessment of Fibre-Matrix Adhesion in Reinforced Polymers by Modal Damping of Guided Acoustic Waves - Claes, Leander; Zeipert, Henning; Brandes, Philipp; Moritzer, Elmar; Henning, Bernd

Validation of Possible Applications of Flake Laminates for Recycling of PA6-CF Production Scrap - Beckmann, Johanna; Bachmann, Andre; Brandes, Philipp; Marten, Thorsten; Tröster, Thomas; Moritzer, Elmar (24th International Conference on Composite Materials (ICCM24))
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche

Creep Effects of Thermoplastic Flange Systems - Bartmann, Finn; Riedl, Alexander; Moritzer, Elmar (Lecture Notes in Mechanical Engineering)

Atmosphärendruckplasma: Grenzflächenmodifikation von Werkzeugstahl: Plasma trifft Stahl: Möglichkeiten zur Modifikation und Verbesserung von Oberflächeneigenschaften - Moritzer, Elmar; Rauen, Dennis; Hoppe, Justin (Magazin für Oberflächentechnik)
Keywords: Plasma; Plasmaaktivierung; Werkzeugstahl

A COMPARISON OF USING FILM INSTEAD OF POLYMER POWDER FOR POLYPROPYLENE GLASS-FIBER COMPOSITE LAMINATES - Moritzer, Elmar; Brandes, Philipp; Wittler, Maurice; Westphal, Max Siegfried (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche

Untersuchung des Erwärmverhaltens von Organoblechen mittels IR-Strahlung für das Fügen im Stempelnietverfahren - Moritzer, Elmar; Völklein, Paul Leonhard (Technomer 2025 29. Fachtagung)
Keywords: Faserverstärkte Kunststoffe (FVK); mechanischens Fügen; Nieten; Organobleche

Berücksichtigung des Kriechverhaltens bei numerischen Simulationen von Thermoplastflanschverbindungen - Moritzer, Elmar; Bartmann, Finn; Riedl, Alexander (1. XXIV Dichtungskolloquium (Essen Juni 2025))
Externer Doktorand von Moritzer

PROCESS DEVELOPMENT OF A POWDER-BASED DIRECT COATING IN THE INJECTION MOLDING PROCESS - Moritzer, Elmar; Lingnau, Kai (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Lackierung; Pulverlack; Spritzgießen

Untersuchung von Kombinationen aus Duroplasten und Elastomeren für den einstufigen 2K-Spritzgießprozess - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (Technomer 2025 - 29. Fachtagung über Verarbeitung und Anwendung von Polymeren)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Thermoset–Rubber 2K Composite Systems: Material Combinations and Interfacial Reactions in a One-Step Injection Molding Process - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

NUMERICAL AND EXPERIMENTAL CONSIDERATIONS OF THE CREEP OF THERMOPLASTIC FLANGE SYSTEMS FOR THE DEVELOPMENT OF AN ANALYTICAL CALCULATION METHOD - Moritzer, Elmar; Bartmann, Finn; Riedl, Alexander (Proceedings of the ASME 2025 Pressure Vessels & Piping Conference PVP2025)

Einfluss von FFF-Prozessparametern auf die elektrische Leitfähigkeit von leitfähigen TPE-Komposite - Salm, Maximilian Karl Franz; Moritzer, Elmar (Technomer 2025 29. Fachtagung)
Keywords: Additive Fertigung; Elektrische Leitfähigkeit; Compounds; TPE; Fused Filament Fabrication

Einfluss der Schichtstruktur auf die Druckfestigkeit von FDM-Bauteilen – Ein konzeptioneller Ansatz - Beutelspacher, Jonas; Scharwald, David; Moritzer, Elmar (Technomer 2025 29. Fachtagung)

Transfer of powder-based direct coating in the injection molding process from two dimensional components to three-dimensional components - Moritzer, Elmar; Lingnau, Kai Martin (The 40th International Conference of Polymer Processing Society)

Werkstofflicher Ansatz zum adhäsiv-basierten Fügen für hochflexible TPE-Organobleche als Verstärkungsstruktur - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)

Influence of the processing parameters on the mechanical strenght of injection moulded BMC components for direct screwing - Held, Christian; Moritzer, Elmar (the 40th International Conference of Polymer Processing Society)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Held, Christian; Moritzer, Elmar (FA11 – Kunststoff-Fügen)